Unlocking the Potential of Battery Electrical Vehicles in West Bengal: An Effective Action Selection Applying Multi-Criteria Group Decision-Making Framework Under Cylindrical Neutrosophic Arena - Barman, Anita; Alam, Shariful; Chakraborty, Avishek (Yugoslav Journal of Operations Research; Online firstDO - 10.2298/YJOR240415023B, 2025)
In the current global scenario, the use of battery electric vehicles (BEVs) becomes very significant for sustainable transportation solutions and reduced carbon emissions. While BEVs have gained much attention as an environmentally friendly form of transport, an enormous research vacuum exists regarding the systematic evaluation and prioritization of different aspects to achieve all the advantages. In our study, we have created “multi-criteria group decision-making (MCGDM)” model that employs both actual and intangible factors to assess and rank different decisions associated with battery vehicle-related obstacles in West Bengal. Here, we applied the power averaging aggregation operator in the Cylindrical Neutrosophic (CN) arena to aggregate the available information. We further discovered that the CN context did not employ the extension of the Best-Worst approach, which is an effective way of dealing with ambiguity in the process of making decisions. Therefore, in this present study, we have proposed Cylindrical Neutrosophic enhanced Best-Worst (CNEBWM) method for assessing the attributes weights and decision-specialists weights in our MCGDM problem. Here, Multiobjective Optimization On the basis of Ratio Analysis (MOORA) and COmbinative Distance based ASsessment (CODAS) are adopted to determine the best action. We have also performed rigorous sensitivity analysis by changing the attribute’s weights to validate the reliability and acceptability of the proposed model. Furthermore, a comprehensive comparison analysis of our model outcome with the well-established previous research works has been presented. Through extensive simulation, we have observed that our proposed MCGDM procedure in a CN circumstance gives stable, resilient, and reliable outcomes when MOORA methodology is followed. This study further demonstrates that, among the four categories of effective actions taken plans (Infrastructure advancement, Incorporating renewable energy, Incentivizing benefits and subsidies, indigenous production and supply chain coordination), infrastructure advancement has been identified as the most crucial factor in case of West Bengal scenario.